Famous but Unknown: Structural Characterization of the Ruthenium-MACHO Catalyst - Jørgensen, Mike S. B.; Enemark-Rasmussen, Kasper; Kubus, Mariusz; Larsen, René Wugt; Nielsen, Martin (Synlett, 2025)
In this work, we present the determination of the crystal structure of the widely used transition-metal complex known as ruthenium-MACHO. The crystal structure of the selectively formed product of the reaction between this complex and hydrogen chloride dissolved in chloroform was also evaluated. The structures determined in this work were compared and evaluated by using various spectroscopic techniques.
Keywords: ruthenium catalyst; ruthenium-MACHO; pincer complexes; coordination chemistry; structure determination; crystal structure